Nursing of Vulvar Cancer Radical Operation Combined with Laparoscopic Inguinal Lymph Node Dissection - Simei Huang; Feifei Qiu (Emergency Medicine International)
Purpose. The application, development, and care of radical surgery combined with laparoscopic inguinal lymph node dissection for vulvar cancer. Methods. We searched the PubMed, Web of Science, the Cochrane Library, and EMBASE databases for published literature on the care of radical surgery combined with laparoscopic inguinal lymph node dissection for vulvar cancer up to June 2022. We used the following search terms and terms: “vulvar cancer,” “injury,” “radical vulvar cancer surgery,” “laparoscopic inguinal lymph node dissection,” and “care.” Results. Laparoscopic inguinal lymph node dissection has become a new surgical method for the treatment of vulvar cancer, and it effectively avoids all the problems associated with traditional surgery. In addition, radical vulvar cancer surgery and laparoscopic inguinal lymph node dissection combined with high-quality nursing interventions can promote patients’ recovery and reduce the occurrence of complications, which has important clinical significance. Conclusion. This article reviews the application, development, and nursing care of radical vulvar cancer surgery combined with laparoscopic inguinal lymph node dissection.